Life roles, values, and careers international findings of the work importance study (Jossey-Bass, 1995)
Life Roles, Values, and Careers answers fundamental questions about the nature of work in modern life based on the research from an innovative, cross-national project of the Work Importance Study. This unique collaborative effort includes data from Australia, Belgium, Canada, Croatia, Italy, Japan, Poland, Portugal, South Africa, and the United States.